Cell blocks prepared from gynaecologic liquid based specimens: as a source for further ancillary techniques - Dr. Shweta Kulkarni; Dr. Nandini Manoli; Dr. Nandish Manoli (Tropical Journal of Pathology and Microbiology, 2018)
Background: Cervical cancer is the second most common cancer among women worldwide and leading causes of cancer deaths amongst women. Cell blocks prepared from liquid-based specimens can serve as a useful adjunct and cell blocks can be further subjected for ancillary molecular techniques. Materials and Methods: In the present study 60 cell blocks were prepared from Manual liquid-basedcytology (MLBC) specimen collected in liquid fixative. Results were compared with cytology smears and histopathological correlation was obtained in 19 cases. P16 and Ki67 were used whenever required. Results: In the present study out of 60 cases of cell blocks 10 cases had no deposit. Of the other 50 cases, 7 cases (14%) were neoplastic and 43(86%) were non-neoplastic. The sensitivity and specificity of cell block, LBC and CPS were 75% and 93%, 66% and 84%, 50% and 70% respectively for neoplastic lesions of cervix. Concordance Rate of CB/Histopathology Vs CPS/Histopathology is 74% vs. 54%. Ki 67 and p16INK4a were used whenever sample was sufficient. Conclusion: In the present study we found that cell blocks prepared from the LBC specimens aid in the diagnosis of neoplastic lesions of cervix and are particularly valuable in distinguishing carcinoma cervix from intraepithelial lesions. Cell blocks can be further subjected to ancillary tools like immunohistochemistry and HPV- DNA testing.